2016
DOI: 10.3109/14764172.2016.1157368
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study analyzing the application of radiofrequency energy and high-voltage, ultrashort pulse duration electrical fields on the quantitative reduction of adipose tissue

Abstract: Noninvasive fat reduction is claimed by many device manufacturers, but proof of efficacy has been difficult to establish. This prospective study was designed to measure the reduction of fat thickness and actual volume reduction in 20 female patients treated with an external radiofrequency (RF) device. This device combines RF heat, suction coupled vacuum, and oscillating electrical pulses that induce adipocyte death over time. Patients underwent pre- and post-treatment and intercurrent measurements of weight, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…Laser treatments have been used for skin rejuvenation and the destruction of solid tumors (Duncan et al, 2016;Sadick and Makino, 2004). Thermal-based interventions aim to precisely damage target tissue by inducing lethal thermal effects that lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Laser treatments have been used for skin rejuvenation and the destruction of solid tumors (Duncan et al, 2016;Sadick and Makino, 2004). Thermal-based interventions aim to precisely damage target tissue by inducing lethal thermal effects that lead to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…RF is an additional technology for noninvasive fat reduction. A study on a radiofrequency device, incorporated with a vacuum feature, reported mean abdominal circumference reduction of 2.3 cm 3 months after the final treatment in 20 patients 29 . SEM on a several human biopsies confirmed structural damage to the cell membrane, suggesting that these pores allow lipid droplets to pass through and lead to cell volume loss 29 …”
Section: Discussionmentioning
confidence: 99%
“…Pinto points out that RF applied at temperatures in the therapeutic range seems to fit into lipolytic intervention, that is, an intervention that leads to adipocyte hypotrophy without causing damage to the cell membrane or inflammation. However, other processes, such as the formation of transient pores in the cell membrane of the adipocyte . This is a process that allows the exit of lipid droplets, with consequent reduction in cellular volume .…”
Section: Discussionmentioning
confidence: 99%
“…However, other processes, such as the formation of transient pores in the cell membrane of the adipocyte . This is a process that allows the exit of lipid droplets, with consequent reduction in cellular volume . As triglyceride breaks down into three fatty acids and one glycerol, their concentration in the blood remains unchanged …”
Section: Discussionmentioning
confidence: 99%